Transcription factors in microalgae: genome-wide prediction and comparative analysis. (December 2016) - Thiriet-Rupert, Stanislas; Carrier, Grégory; Chénais, Benoît; Trottier, Camille; Bougaran, Gaël; Cadoret, Jean-Paul; Schoefs, Benoît; Saint-Jean, Bruno
Abstract Background Studying transcription factors, which are some of the key players in gene expression, is of outstanding interest for the investigation of the evolutionary history of organisms through lineage-specific features. In this study we performed the first genome-wide TF identification and comparison between haptophytes and other algal lineages. Results For TF identification and classification, we created a comprehensive pipeline using a combination of BLAST, HMMER and InterProScan software. The accuracy evaluation of the pipeline shows its applicability for every alga, plant and cyanobacterium, with very good PPV and sensitivity. This pipeline allowed us to identify and classified the transcription factor complement of the three haptophytesTisochrysis lutea, Emiliania huxleyi andPavlova sp.; the two stramenopilesPhaeodactylum tricornutum andNannochloropsis gaditana ; the chlorophyteChlamydomonas reinhardtii and the rhodophytePorphyridium purpureum . By usingT. lutea andPorphyridium purpureum, this work extends the variety of species included in such comparative studies, allowing the detection and detailed study of lineage-specific features, such as the presence of TF families specific to the green lineage inPorphyridium purpureum, haptophytes and stramenopiles. Our comprehensive pipeline also allowed us to identify fungal and cyanobacterial TF families in the algal nuclear genomes. Conclusions This study provides examples illustrating the complex evolutionary history of algae, some of which support the involvement of a green alga in haptophyte and stramenopile evolution.